ANALISIS AKTIVITAS ANTIOKSIDAN SEDIAAN PROPOLIS YANG BEREDAR DI KOTA MAKASSAR DENGAN METODE FRAP (Ferric Reducing Antioxidant Power) - Mamat Pratama; A. Muflihunna; Nurazizah Octaviani (As-Syifaa Jurnal Farmasi, 2018)
Antioxidants are chemical compounds that can donate one or more electrons to free radical, so that free radicals that can be suppressed.This study aimed to obtain and provide scientific evidence to the public regarding the antioxidant activity in propolis liquid product circulating in Makassar. This study using FRAP (Ferric Reducing Antioxidant Power) and 96% ethanol. Free radical activity absorbance was measured with a  UV-VIS spectrophotometer at a wavelength of 710 nm and the total value of antioxidant activity was calculated based on data absorbance. The calculations show that the sample A has antioxidant activity of 0.0971 mgAAE / mg sample, the sample B has antioxidant activity of 0.0669 mgAAE / mg sample, the sample C has antioxidant activity of 0.0493 mgAAE / mg samples.